Nutrition-related parenting practices and child nutritional status in urban and rural settings: A systematic review - Komariah Komariah; Nopi Nur Khasanah; Sri Wahyuni; Herry Susanto; Sri Tutik Rahayu (Lentera Perawat, 2026)
Background: Nutrition-related parenting practices operate within social and geographic environments that shape food availability, caregiving resources, and access to preventive services. Evidence linking these practices to child nutritional status across urban and rural settings remains fragmented and methodologically heterogeneous. Objective: To synthesize evidence on the association between nutrition-related parenting or caregiving practices and nutritional status among children aged 0–12 years, and to examine whether the association differs between urban and rural settings. Methods: This systematic review followed PRISMA 2020 and the Synthesis Without Meta-analysis (SWiM) framework. The last search was conducted on 31 May 2026 in Scopus, PubMed/MEDLINE, SAGE Journals, and ClinicalKey for Nursing for English-language studies published from January 2015 to May 2026.   Results: Eight cross-sectional studies involving 6,062 children or caregiver–child pairs were included; two were secondary analyses of population-based surveys. Three studies were rated low risk of bias and five moderate risk. Rural children consistently had a higher burden of stunting or underweight in comparative studies, but urban–rural differences in feeding practices did not uniformly account for this gap. Delayed complementary feeding and bottle feeding were associated with malnutrition in one Indian study. Grandparenting was associated with malnutrition in rural, but not urban, Chinese children. In other studies, feeding domains showed weak or non-significant associations after adjustment, while child illness, birth weight, maternal nutritional status, household socioeconomic conditions, and service use were more consistent correlates. Conclusion: Nutrition-related parenting practices are relevant to child nutritional status, but their effects are contingent on household resources, child health, and place of residence. The evidence does not support treating urban–rural residence or parenting practice as an isolated causal determinant.